(3GdGbJUGO GdRQGYj (B/s - (3YGQa, LhGO SYOs ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2010)
(3eaGgje GbJUGOjI CSGSjI, Sdhc GdeSJgdc GbJUGOjG h YdGbJg HGdGYdGf GdJLGQj, GdeONd Gdi GdGbJUGO GdRQGYj, GdGbJUGO GdRQGYj h GdGef GdZPGFj, GdRQGYI h NUGFUgG h CfhGYgG, EOGQI GdeRGQY h GdJShjb GdRQGYj, GdGQTGO GdRQGYjP, GdQqj h GdQqj HGdJfbjWs
(3HHdjhZQGajG(B: (3U(B.169s
Keywords: (3GdGbJUGOs; (3GdCef GdZPGFjs; (3GdRQGYI(B- (3GbJUGOjGJs